KEBIJAKAN UPAH MINIMUM UNTUK PEREKONOMIAN YANG BERKEADILAN: TINJAUAN UUD 1945 - Devanto Shasta Pratomo; Putu Mahardika Adi Saputra (Journal of Indonesian Applied Economics, 2011)
The aim of this research is to determine the progress of minimum wage policy inIndonesia, and their linkage to the 1945 Constitution article 27 act 2. The implemen-tation of minimum wage policy in accordance with that constitution, at least shouldbe a few things to do. This includes needs such as decent living as a component ofminimum wage determination. Furthermore, it needs to fill the necessity of transpar-ent effort and intense socialization of benefit provision in the minimum wage. Inaddition it must be clear about the protected status of workers in minimum wagepolicy. The last is the enforcement and strict penalties for companies that do not applythe appropriate minimum wage policy.Keywords: 1945 Constitution article 27 act 2, Minimum Wage Policy, Enfrocement,